Priority Rules, Internalization, and Payment for Order Flow - Degryse, Hans; Karagiannis, Nikolaos (The Review of Asset Pricing Studies, 2025)
Abstract Internalization happens when orders submitted through the same broker are intentionally matched to each other on-exchange or off-exchange. We study the impact of allowing (modes of) internalization on trading rates, investor welfare, and payment for order flow (PFOF). Internalization affects the choice between limit orders and market orders and the participation of dealers in trading. Greater dealer participation creates a greater scope for PFOF. A crucial determinant is the size of the tick. For small ticks, compared with the absence of internalization, its presence leads to higher trading rates, lower investor welfare, and more PFOF. The opposite holds for wide ticks. (JEL G10)